A Comparative Study of the Heat Input During Laser Welding of Aeronautical Aluminum Alloy AA6013-T4 - Coelho,Bruno Nazário (2018)
ABSTRACT The heat input is the amount of energy supplied per unit length of the welded workpiece. In this study, the effect of two different heat inputs in laser beam welding of a high strength aluminum alloy AA6013-T4 was evaluated from macrostructural and microstructural points of view. The experiments were performed using a continuous wave 2 kW Yb-fiber laser with 100 µm spot size on the upper surface of the workpiece. Keeping the heat input at a given level, 13 or 30 J/mm, the laser power was changed from 650 W to 2 kW and the welding speed from 33 to 150 mm/s. In the condition of higher heat input 30 J/mm it was possible to obtain both cutting and welding processes. For 13 J/mm, welding processes were obtained in conduction and keyhole modes. The equiaxed grain fraction changed with changing speed for the same heat input. The laser processing induced a decrease in the hardness of the weld bead of about 25% due to the solubilization of the precipitates. The estimated absorptivities of the laser beam in the liquid aluminum changed largely with experimental conditions, from 4.6% to 10.5%, being the most significant source of error in measuring the real amount of energy absorbed in the process. For the same heat input the macrostructure of the welded surfaces, i.e., humps and dropouts, changed as well. All these facts indicate that the heat input is not a convenient method to parameterize the laser beam welding parameters aiming the same weld features.